2021
DOI: 10.1186/s12885-021-07896-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of breast cancer risk genes and establishment of a prediction model based on estrogen metabolism regulation

Abstract: Background Multiple common variants identified by genome-wide association studies have shown limited evidence of the risk of breast cancer in Chinese individuals. In this study, we aimed to uncover the relationship between estrogen levels and the genetic polymorphism of estrogen metabolism-related enzymes in breast cancer (BC) and establish a risk prediction model composed of estrogen-metabolizing enzyme genes and GWAS-identified breast cancer-related genes based on a polygenic risk score. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…CYP1B1 (cytochrome P450, family 1, subfamily B, polypeptide 1) is an enzyme that catalyzes 17β-estradiol to 4-OHE2 [ 25 ]. CYP1B1 is abnormally highly expressed in a variety of cancers (e.g., breast cancer, head and neck cancer, and PCa), and its effect on reducing the drug sensitivity of tumor cells has been widely reported [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CYP1B1 (cytochrome P450, family 1, subfamily B, polypeptide 1) is an enzyme that catalyzes 17β-estradiol to 4-OHE2 [ 25 ]. CYP1B1 is abnormally highly expressed in a variety of cancers (e.g., breast cancer, head and neck cancer, and PCa), and its effect on reducing the drug sensitivity of tumor cells has been widely reported [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…HAAO has been reported to be associated with endometrial cancer and prostate cancer, but it has not been reported in NPC. CYP1B1 (cytochrome P450, family 1, subfamily B, polypeptide 1) is an enzyme that catalyzes the conversion of 17β-estradiol into 4-OHE2 [ 40 ]. CYP1B1 is abnormally highly expressed in various cancers in various cancers (e.g., breast, head and neck cancers and prostate cancer) [ 41 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…eQTL, expression quantitative trait loci. enzyme function, in lower levels of 4-OH-E2 and lower corresponding adduct production, thereby reducing breast cancer risk (Qiu et al, 2018;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 1B1 (CYP1B1), a member of the second subfamily of cytochrome P450 family I, is a crucial metabolic enzyme in humans ( Cavalieri and Rogan, 2006 ), and high expression levels of CYP1B1 were found in breast, ovarian, and uterine tissues ( Saini et al ., 2009 ; Min et al ., 2022 ). As a critical factor in the initiation and development of hormone-related malignancies, CYP1B1 catalyzes the conversion of 17-estradiol to 4-hydroxylated estradiol (4-OH-E2), thus playing a central role in estrogen metabolism ( Gajjar et al ., 2012 ; Zhao et al ., 2021 ). In breast cancer, 4-OH-E2 goes through a redox cycle that results in the production of oxides as well as chemically reactive estrogenic semiquinone and quinone intermediates (e.g.…”
Section: Introductionmentioning
confidence: 99%